Development of Digital Teaching Materials Based on Betawi Local Food to Increase Ecoliteracy in Elementary School Students - Niken Vioreza; Nana Supriatna; Kama Abdul Hakam (UIN Siber Syekh Nurjati Cirebon, 2022)
AbstractEcoliteracy is an awareness about the importance of saving the environment from potential hazards. Consuming local food is part of ecoliteracy which can be introduced through digital teaching materials. This research aims to produce such materials based on Betawi local food to increase ecoliteracy in elementary school students. The approach used was research and development involving 52 grade IV elementary school students from two different schools in East Jakarta for a small-scaled trial. Product validation was carried out through qualitative descriptive analysis by classifying information from inputs, suggestions, responses, and criticisms acquired from data collection instruments. Quantitative descriptive data was also used to process data obtained through tests and questionnaires in the form of descriptive percentages. Results show that digital teaching materials based on Betawi local food can be implemented in learning and can increase student ecoliteracy effectively in the aspect of head (cognitive). Based on these results, the product is ready to be implemented on a large scale and can be enhanced to increase students’ ecoliteracy.Keywords: digital teaching materials, Betawi local food, ecoliteracy.AbstrakEcoliteracy merupakan kesadaran akan pentingnya melindungi lingkungan dari potensi kerusakan. Mengonsumsi pangan lokal merupakan bagian dari ecoliteracy yang dapat diperkenalkan melalui bahan ajar digital. Penelitian ini bertujuan untuk menghasilkan bahan ajar digital berbasis pangan lokal Betawi untuk menumbuhkan ecoliteracy siswa sekolah dasar. Pendekatan yang digunakan adalah research and development yang melibatkan 52 siswa kelas IV sekolah dasar dari dua sekolah yang berbeda di Jakarta Timur untuk uji skala kecil. Validasi produk dilakukan melalui analisis data deskriptif kualitatif yang dilakukan dengan mengelompokkan informasi berupa masukan, saran, tanggapan, dan kritik yang terdapat dalam instrumen pengumpulan data. Data deskriptif kuantitatif juga dilakukan untuk mengolah data yang diperoleh melalui tes dan angket dalam bentuk persentase deskriptif. Hasil penelitian menunjukkan produk bahan ajar digital berbasis pangan lokal Betawi dapat diimplementasikan dalam pembelajaran dan efektif menumbuhkan ecoliteracy siswa pada aspek head (kognitif). Berdasarkan hasil tersebut, bahan ajar siap diimplementasikan pada skala besar dan dapat dikembangkan untuk menumbuhkan ecoliteracy siswa.Kata kunci: bahan ajar digital, pangan lokal Betawi, ecoliteracy.